PENERAPAN KONSEP MODULAR DENGAN GAYA INDUSTRIAL DI GALERI KOPI EKOWISATA MANGLAYANG BANDUNG - Hayati, Dyah Kumala; Kusnaedi, Iyus (Universitas Ciputra Surabaya, 2024)
The quality and uniqueness of Indonesian coffee have been globally recognized, yet it is unfortunate that the understanding of coffee, especially among the communities around Manglayang, is very limited. Despite Indonesia’s significant potential in the coffee industry, this potential cannot be fully achieved and utilized due to the low awareness among Indonesian society, particularly in the ecotourism coffee area of the Manglayang farmer group, regarding the high quality of coffee products and their minimal knowledge about the coffee products of the Manglayang farmer group. Therefore, there is a need for educational facilities so that the public can understand the quality of coffee from the Manglayang farmer group. The available facilities and infrastructure in the Manglayang farmer group are still inadequate. Thus, this coffee gallery is designed with the aim of providing adequate educational facilities and infrastructure. The coffee gallery is also equipped with supporting facilities such as a CoffeeShop and a Merchandise Store. The abundance of facilities and infrastructure in the design of this coffee gallery is one of the limiting factors for visitor circulation. The solution to this issue is to apply a modular concept to the design of the coffee gallery display. This modular concept will be combined with an industrial style. In the design of the coffee gallery display, the design by research method is utilized